Zoom.us and its potential to generate meaningful learning in direct and indirect restorative dentistry: Unprecedented experience. - Saravia-Rojas, Miguel Ángel (2021)
COVID-19 generated a health emergency that prevented classroom attendance in higher education, affecting the academic development of the teaching of dentistry and all sciences. This gave rise to academic organizations to organize themselves adequately to respond quickly and in a timely manner to be able to take on these new challenges. The use of video conference platforms to replace the usual master classes was the response that was obtained and its implementation was carried out in the shortest time. The result of this implementation forced academic institutions to decide for some of them to respond effectively to the new challenge. In the experience we share our experience with the Zoom.us platform during the CIA I Adult Comprehensive Clinic and CIA III Adult Comprehensive Clinic courses given to the students of the 5th and 7th semesters of the Stomatology career in our house of studies. In this experience, the perception of the use of the tools that said platform has and how they help to generate meaningful learning experiences is shared.